2015
DOI: 10.1517/13543776.2015.1051727
|View full text |Cite
|
Sign up to set email alerts
|

Podophyllotoxin derivatives: a patent review (2012 – 2014)

Abstract: After the successful development of etoposide and teniposide there has been considerable interest in the PPT skeleton to develop newer chemotherapeutic agents. In this regard, several PPT derivatives such as TOP53, GL331, NK611, F11782, and so on, have been developed and are undergoing clinical trials. However, its low natural abundance is a major problem in carrying out research on PPT skeleton. This issue is expected to be addressed with the development of newer synthetic strategies to access structurally mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…Until recently, the knowledge about its biosynthetic pathway was fragmented and key enzymes and corresponding genes were not known (Kumar et al, 2015). A thorough knowledge of complete biosynthetic pathway would ease the access to podophyllotoxin and its natural derivatives which are difficult to produce synthetically (Kamal et al, 2015). Lau and Sattely (2015) have been able to fill the major gaps in the podophylltoxin biosynthetic pathway with the identification of six new enzymes catalyzing the key steps of podophyllotoxin production (Figure 3).…”
Section: Screening For Bioactive Compoundsmentioning
confidence: 99%
“…Until recently, the knowledge about its biosynthetic pathway was fragmented and key enzymes and corresponding genes were not known (Kumar et al, 2015). A thorough knowledge of complete biosynthetic pathway would ease the access to podophyllotoxin and its natural derivatives which are difficult to produce synthetically (Kamal et al, 2015). Lau and Sattely (2015) have been able to fill the major gaps in the podophylltoxin biosynthetic pathway with the identification of six new enzymes catalyzing the key steps of podophyllotoxin production (Figure 3).…”
Section: Screening For Bioactive Compoundsmentioning
confidence: 99%
“…7,8 Similarly, many other modern chemotherapeutic agents have been isolated from plants to treat cancer in clinical situation successfully. [9][10][11][12][13] Recently, scientists and medical professionals have shown increasing interest in this field as they recognize the true health benefits of herbal medicine, which has been playing an important role in the human healthcare since time immemorial.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that PPT exhibits a wide range of pharmacological properties, including insecticidal, cathartic, antirheumatic, antiviral, and especially antitumor activities (Gordaliza, García, del. Corral, Castro, & Gómez-Zurita, 2004;Kamal, Hussaini, Rahim, & Riyaz, 2015). It shows strong cytotoxic activity against a broad-spectrum of cancer cell lines at the cellular level, and is effective in the treatment of wilms tumors, various genital tumors, non-Hodgkin's lymphomas, and lung cancer (Imbert, 1998;Subrahmanyam et al, 1998;Utsugi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%